Green-assisted synthesis of highly defective nanostructured Fe-doped SnO2: Magnetic and photocatalytic properties evaluation - da Silva Ribeiro, M. H.; Marques, G. N.; Moreira, A. J. [UNESP]; Oliveira, M. M.; Oliveira, R. C.; da Silva, R. T.; Krohling, A. C.; Macedo, W. A.A.; Bernardi, M. I.B.; Mascaro, L. H.; Rangel, J. H.G.; de Carvalho, H. B. (Elsevier, 2024)
Here we present a comprehensive characterization of the properties of undoped and Fe-doped SnO2 nanoparticles prepared with Syzygium cumini leaves extract. The phytochemicals present in the leaves extract act as cation chelating and capping of the nanoparticles. It is observed a relative high concentration of tin (up to 10 %) and oxygen (up to 5%) vacancies promoted by surface adsorbed OH− and by Fe-doping, respectively. The magnetic characterization reveals a ferromagnetic with a saturation monetization up to 20×10−3 emu/g for the higher defective and Fe-doped sample. This behavior associated mainly to tin vacancies for the undoped samples, and to the formation of bound magnetic polarons between the incorporated Fe and the oxygen vacancies for the doped samples. Oxygen vacancies and incorporated Fe improve the SnO2 photocatalytic efficiency in the visible range of the electromagnetic spectrum by decreasing the SnO2 effective bandgap from 3.6 eV for the undoped SnO2 sample to only 1.9 eV for the Fe-doped SnO2 sample, and by acting as electron-trapping centers increasing the system quantum efficiency. Due to the ferromagnetic behavior of the studied samples, it was also considered the effect of spin-dependent processes in the observed photocatalytic improvement. Our results highlight the key role of defect engineering strategies to optimize the physical and chemical properties of semiconductor oxides for application in the development of spintronic and quantum information devices, and in systems devoted to wastewater purification through advanced oxidation processes.
Keywords: Defect engineering; Dilute magnetic oxides; Green-assisted synthesis; Multifunctionality; Photocatalysis; Spin-dependent photocatalysis